Prinsip Keadilan dan Kebebasan dalam Pemikiran Ekonomi M. Umer Chapra - Hutagaluh, Oskar; Muin, Rahmawati (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
This research was motivated by researchers' interest in the figure of Umer Chapra as one of the leading figures in Islamic economics and finance. One of Chapra's deep and critical ideas is about usury or bank interest which he put into a small book entitled "Prohibition of Interest: Does it make sense?". This work was quite "impressive" for Chapra because it was written at the request of many people who wanted to see Chapra's critical review regarding bank interest. This research aims to examine various main ideas that dominantly exist in Chapra's economic thinking in the book "The Prohibition of Interest". This research is a study with a qualitative paradigm and is also included in library research. The primary source for this research was obtained from Chapra's original work, while the secondary source came from the works of other people who studied Chapra's thinking, both from research, book reviews and other articles. There are various interesting views discussed by Chapra on economic problems. However, overall, it is revealed that Chapra's thinking in an economic context basically carries the principles of justice and freedom, as part of the principles of Islamic economics.